Methods of Measuring Blood Haematocrit Levels - Bazarova Fariza Ravshanovna; Asqarova Zebo Zafarovna; Xudoyorova Dildora Raximovna (Genius Journals, 2023)
The article considers the methods of blood haematocrit level measurement, their advantages and disadvantages are given. The prospects of development of conductometric methods of haematocrit measurement and implementation of these methods are described. Haematocrit is the ratio of the total volume of blood form elements to the total volume of blood. Changes in the level of blood haematocrit may indicate the presence of such pathological conditions as erythrocytosis, leukaemia, dehydration (increase in haematocrit), anaemia, hyperhydration (decrease in haematocrit). Especially important is the need to control the haematocrit level during haemodialysis procedures
Keywords: Haematocrit; form elements; anaemia